Integração financeira na Europa do euro: avanços, desafios, perspectivas - Ito, Elcio Mitsuhiro (2009)
This research analyzes the development of the financial integration in the euro area, a decisive process for the consolidation of the new common currency and the European Union itself. Since the beginning of the monetary union process, it was assigned to the financial integration the fundamental role for the countries to extract the maximum benefits from the monetary union with the least cost possible. Given the low labor mobility and lack of fiscal coordination within the euro zone, the financial integration received special attention as a mechanism to soften macroeconomic asymmetric shocks via reallocation of resources among segments and companies in the financial markets. Moreover, financial integration allows a more efficient transmission of monetary policies and also allows risk sharing within the monetary union. As a result, new members to the European Union do not necessarily need to wait to have symmetric business cycles before joining the euro. This research presents a selective review of main studies about measuring of financial integration and its current situation in the various segments of the financial markets in the euro area. We conclude that material improvements in the financial integration have been achieved after 10 years of the euro however further challenges are still present mainly in the stock market and retail banking sectors. The recent financial turmoil, which was originated in the U.S. during mid 2007, has resulted in inflexion of the trend in some financial integration indicators but it is still premature to affirm whether this is a trend reversal or a temporary movement